INQUIRING THE NEO-IMPERIAL IDEOLOGY IN THE ENGLISH DEPARTMENT CURRICULUM: TEACHING FOR READING AGAINST THE GRAIN USING READER-RESPONSE - Dewi Candraningrum Soekirno (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
<!-- /* Font Definitions */ @font-face {font-family:"MS Mincho"; panose-1:2 2 6 9 4 2 5 8 3 4; mso-font-alt:"Ã¯Â¼ÂÃ¯Â¼Â³ Ã¦ËÅ½Ã¦ÅÂ"; mso-font-charset:128; mso-generic-font-family:modern; mso-font-pitch:fixed; mso-font-signature:-1610612033 1757936891 16 0 131231 0;} @font-face {font-family:SimSun; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-alt:Ã¥Â®â¹Ã¤Â½â; mso-font-charset:134; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 135135232 16 0 262145 0;} @font-face {font-family:"@SimSun"; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-charset:134; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 135135232 16 0 262145 0;} @font-face {font-family:"@MS Mincho"; panose-1:2 2 6 9 4 2 5 8 3 4; mso-font-charset:128; mso-generic-font-family:modern; mso-font-pitch:fixed; mso-font-signature:-1610612033 1757936891 16 0 131231 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:Arial; mso-fareast-font-family:"MS Mincho"; mso-bidi-font-family:"Times New Roman";} tt {font-family:"Courier New"; mso-ascii-font-family:"Courier New"; mso-fareast-font-family:SimSun; mso-hansi-font-family:"Courier New"; mso-bidi-font-family:"Courier New";} @page Section1 {size:595.3pt 841.9pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Abstract: The spread of the so-called ‘indispensable language’ for the immersion of English in the global world has mesmerized its victims in the classrooms through the operation of curriculum, material, and teaching methodology. Since the perspective of the traditional/structuralism school could not provide enough ‘reader involvement’, reader-response is one of the alternatives that support teaching against the grain. It provides the students with a more active exploration of the text in relation to their selves. This active engagement is important from the perspective of pedagogy. It enriches ‘student-centered’ methodology. The application, however, must be combined with a critical perspective. This process encourages students to identify the position of power in the literary texts. It allows teachers to explore students’ responses that will obviously become invaluable resources in the teaching-learning process.